Nilai Gotong Royong dan Peduli Lingkungan dalam Tradisi Sedekah Bumi Sebagai Sumber Belajar IPS - Siti Romla; Reza Furi Bella Agatha; Ayu Indah Pratiwi; Nur Maulidatur Rohma; Ila Maisyaroh (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2025)
Offering food and drink to the ground as a ritual has been practiced by the Javanese people since long ago, when they were still a very small nation. Beyond that, there is a deeper significance to this tradition: it is a ritual well ingrained in Javanese culture that represents the value of passing on the specific knowledge and experience of the island's farming and fishing groups. One of the goals of this piece is to explain how the earth alms tradition places an emphasis on helping one another out. (2) Explain how the earth alms tradition views environmental protection as an important priority. This study used a literature review as its research model. Seventeen papers published in the recent decade are pertinent to the current investigation. Constantly lending a hand and working in tandem are teachings of the earth alms tradition. Examples of the value of caring for the environment are reflected, namely not just cutting down banana trees, and cleaning up rubbish from activities.